Collagen immobilization on ultraviolet light-treated poly(ethylene terephthalate). (August 2015) - Drobota, Mioara; Aflori, Magdalena; Gradinaru, Luiza M.; Coroaba, Adina; Butnaru, Maria; Vlad, Stelian; Vasilescu, Dan S.
The present article is focused on the studies regarding the effects of ultraviolet (UV) light on poly(ethylene terephthalate) (PET) films surfaces using scanning electron microscopy (SEM), Fourier transform infrared, X-ray photoelectron spectrometry (XPS), and atomic force microscopy (AFM) measurements, subsequent to collagen immobilization. UV treatment influences the surface energy of polymers as the result of the polymer chain breaking, followed by insertion of oxygen-containing functional groups. Accordingly, after UV light treatment, collagen was adsorbed on the PET surfaces in different proportions. Significant changes in the surface topography appeared after collagen immobilization on UV-treated PET films, and they were put in evidence by SEM and tapping-mode AFM experiments. XPS measurements demonstrated the adsorption of collagen on PET UV light-altered surfaces by increasing of nitrogen content. The cytocompatibility tests using stem cells have shown good results for all treated polymers.